The Influence of Tourism Infrastructure and Online Promotion Of Tourist Visit Intention : Study on the Island of Bali with Tourist Satisfaction as an Intervening Variable - Sufa, Siska Armawati; Setiawati, Dewi; Nur Afiat, Muhammad; Rijal, Syamsu (International Journal of Business, Law, and Education, 2024)
This research investigates the influence of tourism infrastructure and online promotion on tourist visit intention, with tourist satisfaction as an intervening variable, focusing on the Island of Bali. A quantitative approach using a cross-sectional survey design was employed, gathering data from 110 tourists. The results revealed significant positive relationships between tourist infrastructure and visit intention, online promotion and visit intention, as well as tourist infrastructure and satisfaction. The mediation analysis confirmed the mediating role of tourist satisfaction. These findings highlight the interconnectedness of infrastructure, digital marketing strategies, and visitor satisfaction in shaping tourist behavior and destination experiences. The study underscores the importance of a holistic approach to destination management that integrates infrastructure development, effective online promotion, and a focus on enhancing visitor satisfaction for sustainable tourism growth.